Acceptability of geothermal installations: A geoethical concept for GeoLaB. (May 2018) - Meller, C.; Schill, E.; Bremer, J.; Kolditz, O.; Bleicher, A.; Benighaus, C.; Chavot, P.; Gross, M.; Pellizzone, A.; Renn, O.; Schilling, F.; Kohl, T.
Highlights: GeoLaB is conceived as the first geothermal reservoir simulator dedicated to reservoir technology and borehole safety. Transparent research guarantees quality control of GeoLaB projects and is an important means of exchange with stakeholders. GeoLaB is a platform for capacity building, science communication, participation and dialogue with all relevant stakeholders. GeoLaB combines pioneering fundamental and applied research with social perception, bridging laboratory to field scale. Abstract: The growing demand for energy, natural resources and urban expansion during the last two centuries increased human interference with the geosphere far beyond geothermal usage. The increasing number of large-scale projects intervening the area of life of communities raised public concerns related to their environmental and social impact. Integration of public concerns into such projects should therefore go beyond outreach and communication measures. It requires an open approach to inclusive governance structures with respect to designing research and development processes and to modify technological options. Geoethical concepts emphasize that geoscientific knowledge may assist society in decision making as well as in dealing with risks, user conflicts and environmental threats on local, regional and global scale in order to support more sustainable practices at the intersection of human beings and the geosphere. In the present article, we analyse the social response to recent geothermal development and identify the precondition for public acceptability of geothermal projects. On this basis, the potential contribution of a GeoLaB, aGeo thermalLa boratory in the crystallineB asement, to a geoethic approach in geothermal research and technology development is discussed. The underground research laboratory is planned as an infrastructure to answer scientific challenges and to offer the necessary transparency to interact with the public. The GeoLaB approach aims on transparent, tangible science and can serve to enhance mutual understanding of stakeholder groups. It may increase public awareness on geothermal research and potentially enhance the opportunity for public approval of planned activities. As a generic site, GeoLaB can develop scientific-technological solutions for a responsible exploitation of geothermal energy accompanied by sociological studies. The underground research laboratory will serve as a platform for science communication, participation and dialogue of stakeholders from industry, politics, administration and society. This complies with the comprehension of responsible research in a geoethical sense.